Weighted Maximum Likelihood Approach for Robust Estimation: Weibull Model - Khokan, Mahfuzur Rahman; Bari, Wasimul; Khan, Jafar A (Dhaka University Journal of Science, 2013)
A robust weighted maximum likelihood (WML) estimation approach is proposed for the Weibull model in the presence of outliers. Extensive simulation studies are conducted to examine the performance of the proposed approach and simulated results reveals that the WML approach provides better results compared to the usual maximum likelihood (ML) approach in the presence of outliers. DOI: http://dx.doi.org/10.3329/dujs.v61i2.17061 Dhaka Univ. J. Sci. 61(2): 153-156, 2013 (July)